2017
DOI: 10.15171/jnp.2017.26
|View full text |Cite
|
Sign up to set email alerts
|

Sodium hydrogen sulfide (NaHS) ameliorates alterations caused by cisplatin in filtration slit diaphragm and podocyte cytoskeletal in rat kidney

Abstract: Background: Hydrogen sulfide (H2S) has been shown to have a protective role in various kidney disorders. Objectives: This study investigated the molecular mechanism of NaHS (a H2S donor) in treating on the renal damage induced by cisplatin (CP).Materials and Methods: Thirty-two male rats were randomly divided into 4 groups: Normal control group (group A)‚ NaHS group (group B) which received 200 µg/kg/d (intraperitoneal injection; i.p.) for 15 days‚ CP group (group C) which rats were injected with CP (5 mg/kg, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…Apoptosis is an important factor in the pathogenesis of CDDP-induced AKI [ 6 , 7 ]. Under normal circumstances, apoptosis is a permanent and fundamental form of programmed cell death that occurs in multicellular organisms [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Apoptosis is an important factor in the pathogenesis of CDDP-induced AKI [ 6 , 7 ]. Under normal circumstances, apoptosis is a permanent and fundamental form of programmed cell death that occurs in multicellular organisms [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Liu and colleagues used GYY4137 at a low dose of GYY4137 (21 mg/kg) in mice, and it is highly probable that H 2 S might be insufficiently provided at lower concentrations considering the H 2 S release characteristics of GYY4137 [ 51 , 52 , 53 ]. On these grounds, a commonly used dose of GYY4137 (100 mg/kg; dissolved in PBS) was prepared in our animal studies, and GYY4137 largely ameliorated cisplatin-induced renal dysfunction and damage, which is in-keeping with the results of NaHS (another H 2 S donor) application in animals [ 54 , 55 , 56 ]. These results clearly demonstrated the protective actions of H 2 S donors against cisplatin-induced nephrotoxicity.…”
Section: Discussionmentioning
confidence: 73%
“…Alternatively, it has been reported that treatment with GYY4137 and NaHS exert antitoxicity effects through the reduction of ROS and the inhibition of nicotinamide adenine dinucleotide phosphate and MAPK activities in cisplatinadministered porcine renal proximal tubule cell line LLC-PK1 . NaHS can also upregulate the expression of nephrin and reduce the level of desmin (Karimi and Absalan, 2017). In addition, treatment with diallyl disulfide (DADS) alleviates nephrotoxic effects of cisplatin by increasing antioxidant defense and suppressing apoptotic, oxidative, and inflammatory activities (Elkhoely and Kamel, 2018).…”
Section: Drug-induced Nephrotoxicitymentioning
confidence: 99%
“…Kidney works together with the renin-angiotensin-aldosterone system (RAAS) to regulate BP and maintain electrolyte balance ( Cortinovis et al, 2016 ). The decline in BP and Na + level or the stimulation of β1-adrenoreceptors can result in the secretion of renin, which in turn converts angiotensinogen (produced in the liver) into angiotensin-I which is then converted to angiotensin II by angiotensin-I converting enzyme (ACE) ( Soubrier et al, 1993 ; Deschepper, 1994 ). Angiotensin II acts on several receptors to mediate the downstream effects.…”
Section: The Role Of Hydrogen Sulfide In Kidney Physiologymentioning
confidence: 99%